Physiological responses of smooth marron Cherax cainii fed various protein sources substituting with larvae oil of black soldier fly Hermetia illucens (Asian Journal of Agriculture, 2024)
Abstract. Dao TTT, Fotedar R, Howieson J. 2024. Physiological responses of smooth marron Cherax cainii fed various protein sources substituting with larvae oil of black soldier fly Hermetia illucens. Asian J Agric 8: 104-115. A ten-week feeding experiment was conducted to examine the impact of using Black Soldier Fly Larvae (BSFL) oil as a substitute for Fish Oil (FO) on the growth and health of smooth marron (Cherax cainii Austin & Ryan, 2002). Six diets were formulated with varying protein and lipid sources: D1 (fish meal [FM] + FO + canola oil), D2 (FM + BSFL oil), D3 (poultry by-product meal + BSFL oil), D4 (defatted BSFL meal + BSFL oil), D5 (lupin meal [LM] + BSFL oil), and D6 (LM + FO + BSFL oil). Marron was randomly distributed among the dietary treatments, which had three replicated tanks per treatment. Growth, immune response, and organosomatic indices were measured. Marron fed on lupin meal and BSFL oil (D5) exhibited reduced growth and immune response. Marronfed D2, D3, and D4 exhibited significantly higher protease activity compared to other diets. Feed water stability was highest in D1 and D2, and shortest in D5 and D6. The hepatosomatic index and hepatopancreas moisture content varied among diets, but there were no significant differences in tail muscle indices. In conclusion, BSFL oil can replace FO in animal protein-based diets, but FO is still needed when lupin is the main protein source.
Keywords: Black soldier fly larvae oil, fish oil, growth performance, smooth marron Cherax cainii, various protein sources